Visibility and Clausal Arguments - van Gelderen, Elly (Linguistica Atlantica, 1990)
This paper examines the Visibility Principle (cf. Chomsky 1981; 1 986a), which deals with the assignment of theta-roles to elements visible by means of Case. Because it requires arguments to have Case and predicates not to have Case, the principle, in its strong form, is broader than the Case Filter. The assumption that CPs and IPs do not have Case would weaken the Visibility Principle; however, evidence advanced here indicates both that CPs must be Case-marked and that IPs must be visible. Burzio's Generalization, which resembles the Visibility Principle, is examined and reformulated.